Case Study Teaching Method in Tertiary Education: A Solution for Addressing the Theory - Practice Gap - Huong, Nguyen Thi (VNU Journal of Science: Education Research, 2020)
This paper reviews the concept of case study teaching method, its purposes, techniques and procedures. The paper also presents a real-life example of case study teaching method that has been applied in tertiary education overseas. The paper concludes that appropriate application of case study teaching method as well as the development of a case study database in Vietnamese universities will be an arguably viable solution to improve education quality and to bridge the gap between theory and practice.